THE ANAMORPH OF SARAWAKUS SUCCISUS RIFAI - Rifai, Mien A.; Basuki, Triadi; Karmadibrata, Kartini (REINWARDTIA, 1984)
Single ascospore isolates of Sarawakus succisus Rifai produce a Trichoderma like anamorph. The hypocreaceous nature of the genus Savawakus Lloyd is therefore indicated. A detailed illustrated description of this conidial state is presented.